Prispevek k poznavanju steklokrilcev (Lepidoptera: Sesiidae) v Sloveniji - Predovnik, Željko (Acta entomologica slovenica (Ljubljana), 2001)
12 species of clearwing moths have been found, not mentioned in the List of macrolepidoptera in Slovenia. As these species are also distributed in the neighbouring countries; the finds were expected. All 12 taxons are already mentioned in literature, but with no exact data.
Keywords: favna; Lepidoptera; metulji; Slovenia; Slovenija; steklokrilci